Navigating Dual-Structured Crisis: Factors Influencing Nonprofit Organizational Resilience - Vien, Ha B.; Hoang, Thanh Thi (Nonprofit and Voluntary Sector Quarterly, 2026)
The COVID-19 pandemic constituted an unprecedented exogenous shock to many nonprofit organizations, testing their ability to sustain operations and adapt to crises. Building on population ecology and nonprofit organizational resilience framework, this study conceptualizes COVID-19 as a dual-structured crisis and examines how organizational factors, coupled with resilience tactics, shape nonprofit resilience. Results from 169 nonprofits highlight that specialist organizations (art and culture) are more vulnerable to external crisis than generalist nonprofits (human services). While donor support was critical for sustaining human-service organizations, peer support from other nonprofits emerged as a key factor for arts and culture organizations. In addition, system-wide constraints muted the effects of traditional strategies such as technology adoption and federal funding access on nonprofit resilience. Our findings underscore the context-dependent effectiveness of resilience tactics and offer new insights into managing nonprofits in future crises.
Keywords: dept.pch

Mandate for Leadership: The Conservative Promise By D.Bakst, J.Berry, L. M.Burke, D. R.Burton, A.Candeub, D. J.Carmack, B.Carr, B. S.Carson, P.Sr., Dans, K.Cuccinelli, R.Dearborn, V.deRugy, D.Devine, D.Furchtgott‐Roth, T. F.Gilman, M. M.Gunasekara, G.Hamilton, J.Hazelton, K.Kerrigan, D. D.Kirk, K.Lassman, B. L.McNamee, C.Miller, S.Moore, M.Namdar, P.Navarro, W. P.Pendley, M.Primorac, R.Severino, K. K.Skinner, B. D.Tucker, H. V.von Spakovsky, R.Vought, W. L.Walton, and P.Winfree, Washington DC: The Heritage Foundation. 2023. pp. ix‐887. ISBN: 978‐0‐89‐195174‐2 - Greenstein, Gabriel (Public Administration Review, 2025)
Keywords: Berry; Biology; Botany; Carr; Humanities; Philosophy; dept.psc

Exploring Perceived Fairness in Performance Evaluation Among Telecommuting Employees in Public Agencies - Aggarwal, Jyoti; Hoang, Thanh (Public Administration Quarterly, 2025)
Keywords: Business; Economics; Engineering; Marketing; Political science; Psychology; Public relations; Public sector; Telecommuting; Work (physics); dept.psc; fairness; federal government; organizational justice; performance evaluation; public sector; telecommute

Oral Hygiene Care of Older Adults and Caregiver Education: A Systematic Review - Asanza, Dachel; Njoku, Anuli; Baviskar, Snehal; Evans, Marian; Mouloudj, Kamel (Hygiene, 2025)
Background: There is a need to develop comprehensive guidelines to encourage the promotion of oral hygiene care among older adults and to assist caregivers in this endeavor, taking into consideration the specific challenges that arise from aging, comorbidities and caregiving. Methods: This review was conducted by searching across relevant literature from meta-databases including Academic Google, PubMed, Scielo and Scopus for studies published from 2020 to 2024. PRISMA guidelines were followed. We included articles that described oral hygiene methods, caregiver education and mechanization status of older adults. Common themes, best practices, and gaps in current guidelines were tracked using extracted and analyzed data. Results: The review revealed multiple factors affecting the oral hygiene of older adults, with themes relating to physical impairment, cognitive dysfunction, and caregiver involvement. Highlighted between the approaches are individualized therapy for oral hygiene, caregiver education, and the use of technology to improve adherence to oral hygiene. Barriers like dental care access, underlying medical conditions complicating dental treatments, and cost considerations were identified. Conclusions: The findings emphasize the necessity of clear recommendations that can help caregivers and advance dental care for older adults.
Keywords: Dental care; Hygiene; MEDLINE; Oral health; Oral health care; Oral hygiene; Promotion (chess); Scopus; aged; caregiver education; caregivers; dentistry; dept.pch; education; frail elderly; healthy aging; older adult; oral health; oral hygiene; oral medicine

Period Poverty Among Black, Hispanic and Low-Income Communities in the United States: Challenges and Recommendations - Njoku, Anuli; Alhassan, Mubarak; Tohura, Sharaban; Garcia, Kayla (Hygiene, 2025)
Period poverty refers to the lack of access to or affordability of menstrual hygiene supplies such as sanitary products and the inaccessibility of washing facilities, waste disposal and educational materials. Period poverty can significantly affect menstruating individuals’ physical, mental, and reproductive health and emotional wellbeing; negatively impact educational outcomes; cause financial strain; result in absenteeism from work and school; create barriers to healthcare access; and perpetuate poor health outcomes for generations. Barriers to menstrual equity include lack of access to period support, cost, poor sanitary facilities, lack of education, social and cultural stigma, and legal restrictions. Therefore, it is crucial to actively advocate for initiatives to increase access to menstrual hygiene products, raise public awareness, and educate individuals on safe menstrual practices. Approximately 500 million girls and women worldwide and an estimated 16.9 million people in the United States experience period poverty, with the issue being particularly common among marginalized groups such as Black or Hispanic menstruating individuals and those who are homeless, living in poverty, of low income, or attending college. This article investigates the physical, psychological, educational and social impacts of inequitable access to menstrual products, menstrual education, and sanitation facilities among menstruating individuals who are Black, Hispanic or of low income within the United States. We examine the threat this poses to health equity and propose recommendations to address this pervasive issue.
Keywords: Absenteeism; Equity (law); Health care; Hygiene; Poverty; Public health; Sanitation; Socioeconomic status; dept.pch; environmental sustainability; gender disparities; health equity; menstrual education; menstrual health; menstrual health management; menstrual hygiene products; period poverty; period tax; polycystic ovarian syndrome (PCOS); poverty alleviation; women’s health

Social justice with harm reduction approaches for mothers who use opioids: an international comparative ethnographic study with community engaged methods - Boeri, Miriam; Lamonica, Aukje; Whittaker, Anne; Bruce, Marisa (Harm Reduction Journal, 2025)
BACKGROUND: Mothers and pregnant women who use opioids are particularly vulnerable. Mothers often fear surveillance, stigma, and loss of custody of their children when seeking treatment. Although opioid agonist therapy (OAT) has been shown to be effective, access varies regionally, and not all mothers can cease using opioids. This study compares outcomes of mothers who use opioids in the UK with universal healthcare and OAT access, and mothers in the U.S. with restricted healthcare and OAT access, focusing on their interactions with services. METHODS: This is a secondary data analysis of two studies on mothers who use opioids. Data were collected from nine mothers in Scotland (UK) and 20 mothers in New Jersey (US) through ethnographic, longitudinal studies spanning one year. The UK study used a "Learning Alliance" engagement approach, a patient/public engagement model that involves stakeholders in developing objectives and the dissemination of findings. The US study engaged "community-based consultants," who are paid individuals with lived experience from the study field communities to assist researchers in recruitment and ethnographic fieldwork. Ethical approval was received from review boards. Data were anonymized before analysis, and people with lived experience provided feedback on findings. Grounded theory methods were used for analysis. RESULTS: Findings reveal both convergent and divergent experiences. Mothers in Scotland had more access to healthcare and social housing but faced increased surveillance, while New Jersey mothers often experienced housing insecurity and difficulty obtaining healthcare. Shared challenges included trust issues, stigmatization, inconsistent practitioner engagement, responsibilization, and unclear expectations from child protection services. While Scottish mothers had better access to OAT, both groups faced child custody loss due to unregulated drug use. Mothers in both studies were struggling to meet reunification requirements of abstinence (with or without OAT) within the required time frame. CONCLUSIONS: Differing governance structures create persistent challenges across national boundaries. While health practitioners generally support harm reduction strategies, it does not go beyond OAT for mothers. Our findings indicate the need for radical harm reduction approaches with social justice for mothers who use drugs, including safer parental drug use strategies.
Keywords: Child protection; Community engagement; Corporate governance; Criminal justice; Economic Justice; Ethnography; Harm; Harm reduction; Health psychology; Mothers who use drugs; Opioids; SAFER; Social policy; dept.pch

President Nixon and Senator Kennedy on Health Care: How Rivalry Shaped Reform - Hopper, Jennifer (Congress & the Presidency, 2025)
Keywords: Economics; Health care; Health care reform; Health policy; Law; Law and economics; Political science; Public administration; Rivalry; Sociology; dept.psc; peer-reviewed

Carving a Space for Elite Republicanism: Hierarchy, Deference and Paternalism in American Political Development - O'Hara, Jonathan (Europolis, Journal Of Political Science And Theory, 2010)
The present article is a review of the American Political Development literature dealing with the issue of national administrative politics and development in late nineteenth century American history. Particular attention is paid to the ways in which historical institutionalists discount the importance of elite republican ideology as an explanation of national administrative growth. Attention is also paid to the ways in which sociological institutionalists view republicanism as a viable ideological alternative only for far flung and marginalized social interest groups. The article argues for studying the ideology also in terms of its elitist tradition and the tradition’s application to national administrative politics and development in the American context, emphasizing categories of hierarchy, deference and paternalism. As a review of seminal works related to the research program of American Political Development, this article is of particular use to those studying American development at the turn of the twentieth century.
Keywords: American politics; United States; dept.psc; elitism; ideology; republicanism

Calvin Coolidge - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

James Buchanan - Hopper, Jennifer (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.People involved or simply interested in politics often ask whether today's political environment is more toxic than ever before. Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump presents an impartial and authoritative history of invective toward the White House so readers can determine the answer for themselves.The book focuses on the most representative and commonplace attacks of a vitriolic and personal nature, detailing who instigated and trafficked in the attacks and how presidents, administrations, and political parties defended themselves. It also illustrates how honest disagreements about policy―such as FDR's New Deal, Ronald Reagan's Central America policies, George W. Bush's invasion of Iraq, and Barack Obama's Affordable Care Act―fueled expressions of hatred and condemnation. Finally, the book includes perspectives from both the right and the left on the legitimacy of these attacks and the victims' defenses as well as their impact on American politics and policy.
Keywords: dept.psc

Same-sex Marriage - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Campaign Finance - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

War on Terror - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Affordable Care Act - Hooper, Jennifer (Encyclopedia of the American Presidency, 2017)
The most up-to-date reference of its kind, Encyclopedia of the American Presidency, Third Edition is the definitive guide to the role of the president from the American Revolution through the present day.
Google-Books-ID: 4EmJwwEACAAJ
Keywords: dept.psc

Diplomatic Amateurs or Qualified Professionals? Profiling the American Ambassador - Calin, Costel; Fitzpatrick, Kathy R. (White House Studies, 2013)
Are U.S. ambassadors qualified to lead America’s diplomatic missions abroad? This age-old question—often raised but seldom seriously considered by diplomacy scholars— is the focus of this study, which examined the professional credentials of American ambassadors appointed by former U.S. President George W. Bush. The article explores the relationship between the professional status of U.S. ambassadors and the power status and economic importance of host countries. The results showed that preferred destinations for amateur ambassadors were mostly Western European countries and countries with which the United States has large economic exchanges. Professional ambassadors were mostly appointed to African and Asian countries and to countries that have lower trade with the United States. The vast majority of semiprofessional diplomats were appointed to the most powerful countries.
Keywords: AMERICAN ambassadors; BUSH; George W. (George Walker); 1946-; DIPLOMATIC & consular service; GOVERNMENT missions; INTERNATIONAL relations; PRESIDENTS of the United States; dept.psc

The US PATRIOT Act (2001) - Buterbaugh, Kevin (Government at Work: Policymaking in the Twenty-First-Century Congress, 2016)
This edited volume features academic experts using leading policy frameworks to analyze the prominent U.S. public policy issues of the twenty-first century. Readers will learn about the similariti...
Keywords: dept.psc

Where are we when the community looks for us? A social network analysis of the self-organized network #TwitterFoodBank - Hoang, Thanh Thi (Communication and the Public, 2023)
Traditional crisis management approaches have often overlooked the role of community and nonprofit organizations. In this study, we investigated how nonprofits and communities contributed to problem-solving during crises through self-organization on social media. We applied social network analysis to 17,732 interactions using #TwitterFoodBank, a self-organized network emerged during the early stage of COVID-19 to address food insecurity. Our results highlighted the significant role of nonprofits in coordinating the community’s self-organized network. However, they also revealed a lack of coordination among these organizations in maintaining a viable network. These findings have valuable implications for nonprofits seeking to leverage the potential of online self-organized communities in crisis management.
Keywords: dept.psc; peer-reviewed

Small Power: How Local Parties Shape Elections by David Doherty, Conor M Dowling and Michael G Miller - Wharton, Jonathan L. (Political Science Quarterly, 2023)
Num Pages: 3
Keywords: book.review; dept.psc

Electoral Realignment and the Outlook for American Democracy. - Sabbatical Report - Paulson, Arthur C. (2006)
Keywords: dept.psc; faculty_collection; sabbatical_report

Employment in the Academe: The Impact of Public and Judicial Opposition to Affirmative Action. - Rai, Kul B. (2003)
Keywords: dept.psc; faculty_collection; sabbatical_report

The Impact of Public and Judicial Opposition to Affirmative Action. - Rai, Kul B. (2003)
Keywords: dept.psc; faculty_collection

Contra the New Deal: Roosevelt and His Critics 1933-1940. - Weed, Clyde (2003)
Keywords: dept.psc; faculty_collection; sabbatical_report

Globalization: People, Politics, and Places. - Critzer, John (2002)
Keywords: dept.psc; faculty_collection; sabbatical_report

Eager to Share?: Women Representatives in Britain, France and the United States. - Applewhite, Harriet (Academic year-2002; Political Science., 2001)
Keywords: dept.psc; faculty_collection; sabbatical_report

“Enquiring Minds Want to Know”: President Bill Clinton and the Blurring of News and Gossip - Hopper, Jennifer (A Gossip Politic: Rhetoric, Politics and Society, 2023)
This chapter explores the case of President Bill Clinton and the Lewinsky scandal as a pivotal moment in the convergence of political, technological, and cultural changes that elevated the presence of gossip and rumor in mainstream news sources, with major, lasting consequences. Throughout the unfolding of the scandal, unconfirmed and often salacious information about what had happened was transmitted among individuals and amplified through the media. The chapter takes a close look at some key elements contributing to such trends, including use of anonymous sourcing, heightened competition between media outlets, and the emergence of new media actors covering American politics and the presidency. An analysis of two specific incidents, involving coverage of allegations there were eyewitnesses to the president’s affair with Monica Lewinsky and that Lewinsky had a dress stained with the president’s DNA in her possession, demonstrates how prominent national news outlets publicized information reflecting weaker reporting standards and conveyed unsubstantiated rumors as news. As the news media devalued itself in cases such as this one, abandoning professional conventions and prioritizing sensational, entertaining content, the public began to no longer trust or rely on such sources to help it interpret events. We continue to see the ramifications of those developments in the present, with widespread belief in fake news, little consensus on what constitute facts or reality, and stark partisan divides about who can be relied upon to transmit the truth of political events. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.
Keywords: New media; President Bill Clinton; Scandal politics; The Lewinsky Scandal; dept.psc

Women Representatives in Britain, France, and the United States - Applewhite, Harriet Branson (Palgrave Macmillan, 2015)
"This book compares British, French, and American legislative debates on woman suffrage and women's rights. Beginning with an analysis of Tocqueville and J.S. Mill on the impact of suffrage, the book continues with analysis of floor debates, comparing gender style, the French on parity and the Americans on the ERA and concluding with modern debates"–
Keywords: France; Women; France; Women legislators; Great Britain; Women; Great Britain; Women legislators; History; Women; Suffrage; United States; United States; Women legislators; Women; dept.psc; faculty_collection

Professional Pathways to the Presidency - Marchant-Shapiro, Theresa (Palgrave Macmillan, 2015)
"During presidential elections a quadrennial debate emerges which, although it differs in the particulars, reflects the same structure in each reincarnation. Although the issue positions taken by the candidates vary over the years, their claim to qualification for the presidency follows a common pattern. Each candidate discusses his or her prior experience as preparation for one or more of the requirements of the office and then lays claim to the legacy of one of the great presidents who followed the same trajectory to the White House.Missing from this debate is a systematic analysis of how different job experiences prepared the population of all presidents for service. For each of the greats who followed a particular pathway to the presidents there is a failure who shared the pathway. In this book I combine the quantitative evaluation of presidential performance with mixture of qualitative and quantitative analyses of professional qualifications. The recent C-SPAN surveys provide us with a nuanced measure of presidential performance by asking historians to rate the Presidents on ten constituent attributes of: Public Persuasion, Moral Authority, Relations with Congress, Performance within Context of Times, Crisis Leadership, International Relations, Vision/Setting an Agenda, Economic Management, Administrative Skills, and Pursued Equal Justice for All. The sub-score for 'Relations with Congress' measures how well the president performs as 'legislator-in-chief' so that I can see whether former legislators work better with congress. Similarly the measure of 'Administrative Skills' indicates whether experience as a governor leads to better performance as the national chief executive. The evaluation of 'Economic Management' looks at whether those presidents with business experience do a better job in dealing with the economy. C-SPAN's nuanced measure of presidential performance allows a more careful evaluation of how prior experience affects particular aspects of presidential greatness than was previously possible"–, "Presidential hopefuls frequently claim they are qualified because their job experience is the same as a great president. However they ignore the failed presidents who shared the same pathway. This book evaluates all the presidents systematically to determine how prior professional experience influences presidential performance"–
Keywords: History; Vocational qualifications; Political aspects; Presidents; United States; dept.psc; faculty_collection

Statistics for Political Analysis: Understanding the Numbers - Marchant-Shapiro, Theresa (Sage CQ Press, 2014)
Keywords: Statistics; Textbooks; Textbooks; Political statistics; dept.psc; faculty_collection

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, Jonathan L. (Palgrave Macmillan, 2013)
Keywords: Booker; Cory; Metropolitan government; Case studies; Case studies; Mayors; Case studies; Newark (N.J.); Case studies; Post-racialism; Election; African American mayors; New Jersey; Newark; Newark; Urbanization; Political aspects; Politics and government; Newark (N.J.); Race relations; United States; dept.psc; faculty_collection

Lemkovyna: A History of the Lemko Region of the Carpathian Mountains in Central Europe - Polianskii, Ioann; Best, Paul J.; Decerbo, Michael; Maksimovich, Walter (Carpathian Institute, The Lemko Association, 2012)
Keywords: History; History; Carpathian Mountains; History; Lemkivshchyna (Poland and Slovakia); Lemky; dept.psc; faculty_collection

Does a Fourth Rus' Exist?: Concerning Cultural Identity in the Carpathian Region - Best, Paul J.; Stępień, Stanisław (Higganum, 2009)
Keywords: Europe; Eastern; Slavs; Slavs; United States; dept.psc; faculty_collection

The WTO Primer: Tracing Trade's Visible Hand Through Case Studies - Buterbaugh, Kevin; Fulton, Richard M. (Palgrave Macmillan, 2008)
Keywords: 20th century; 20th century; Commercial policy; History; History; General Agreement on Tariffs and Trade (Organization); History; International trade; World Trade Organization; dept.psc

Electoral Realignment and the Outlook for American Democracy - Paulson, Arthur C. (Northeastern University Press ; University Press of New England, 2007)
Paulson's timely and authoritative study incorporates the latest data from the 2000 and 2004 elections into his analysis, and it offers vital perspectives on the outlook for the 2008 election.–(Source of description unspecified.)
Keywords: Election; Elections; Political parties; United States; United States; Presidents; dept.psc

The Lemkos of Poland: Articles and Essays - Best, Paul J.; Moklak, Jarosław (Carpatho-Slavic Studies Group and the Historia Iagellonica Press, 2000)
Keywords: Ethnic relations; History; Poland; Lemky; Poland; dept.psc; faculty_collection

The Aegean Sea After the Cold War: Security and Law of the Sea Issues - Chircop, Aldo E.; Gerolymatos, André; Iatrides, John O. (St. Martin's Press, 2000)
Keywords: Aegean Sea Region; Security; International; Greece; Foreign relations; Greece; Law of the sea; Turkey; Turkey; dept.psc; faculty_collection

Realignment and Party Revival: Understanding American Electoral Politics at the Turn of the Twenty-First Century - Paulson, Arthur C. (Praeger, 2000)
Keywords: Election; Political parties; Presidents; United States; dept.psc; faculty_collection

Affirmative Action and the University Race, Ethnicity, and Gender in Higher Education Employment - Rai, Kul B.; Critzer, John W. (University of Nebraska Press, 2000)
Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and nonacademic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks, Asians, Hispanics, and Native Americans. The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non-elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities. Kul B. Rai is a professor of political science at Southern Connecticut State University. His works include "America in the Twenty-First Century: Challenges and Opportunities in Domestic Politics". John W. Critzer is a professor of political science at Southern Connecticut State University., "Affirmative Action and the University is the only full-length study to examine the impact of affirmative action on all higher education hiring practices. Drawing on data provided by the Equal Employment Opportunity Commission and the U.S. Department of Education's National Center for Education Statistics, the authors summarize, track, and evaluate changes in the gender and ethnic makeup of academic and non-academic employees at private and public colleges and universities from the late 1970s through the mid-1990s. Separate chapters assess changes in employment opportunities for white women, blacks Asian, Hispanics, and Native Americans." "The authors look at the extent to which a two-tier employment system exists. In such a system minorities and women are more likely to make their greatest gains in non elite positions rather than in faculty and administrative positions. The authors also examine differences in hiring practices between public and private colleges and universities."–Jacket.
Keywords: Discrimination in higher education; Employment; United States; United States; Affirmative action programs; United States; Minority college administrators; United States; Minority college teachers; dept.psc; faculty_collection

Trade and the Environment - Buterbaugh, K. (Encyclopedia of Violence, Peace, & Conflict: Volume 1-4, Third Edition, 2022)
This article focuses on the complex interaction between trade and the environment. The first section reviews the debate among scholars on the environmental effects of trade. Next the article examines the role of the World Trade Organization and how its decisions have impacted the environment. This is followed by a discussion of climate change and its connection to trade. Finally, the article examines multilateral efforts to govern trade and control its environmental consequences as well as to encourage sustainable development. © 2022 Elsevier Inc. All rights reserved.
Keywords: Carbon leakage; Climate change; Comparative advantage; Environmental Kuznets curve; Externality; Free rider problem; Multilateral environmental agreements (MEAs); Nontariff barriers to trade; Pollution haven hypothesis; Prisoner's dilemma; The general agreement on tariffs and trade; World trade organization; dept.psc

Abatement Addiction: A Case Study on Jersey City's Municipal Tax Abatements, Urban Gentrification and the Politics of Rights - Wharton, Jonathan (American Political Science Association, Social Science Research Network, 2011)
As New Jersey’s second largest city, Jersey City has experienced a surge in urban redevelopment and new development, particularly its downtown wards closest to New York City. Situated on the Hudson River directly across from downtown New York City, Jersey City is an ideal location for New Jersey developers and realtors to redevelop in order to attract New York City’s financial sector employees and individuals desiring more living space at lower rental or mortgage costs. In other words, downtown Jersey City exemplifies urban gentrification. In the last twenty years, several public policies helped spur waterfront development to attract potentially wealthier residents. In an effort to lure developers and investors, Jersey City officials relied heavily on municipal tax abatements to offset increasingly high property taxes. So after two decades, has Jersey City demonstrated that Payment in Lieu of Taxes (PILOT), tax abatements and other tax policy incentives are in fact feasible in terms of the following questions: What have been the implications of these policies? Who benefited from and who was marginalized from these policies? This paper examines the rising concerns surrounding tax abatements and other pro-development tax policies. By examining a medium sized city like Jersey City, this case study is especially useful in understanding the significant issues and shortcomings with urban redevelopment tax incentives. Too often these incentives benefit a political and financial elite at the economic expense and loss of political rights of long-term residents and renters.
Keywords: New Jersey; dept.psc; gentrification; tax abatements; urban development; urban politics; ⛔ No DOI found

A Post-Racial Change Is Gonna Come: Newark, Cory Booker, and the Transformation of Urban America - Wharton, J. (Springer, 2013)
This work offers a political and historical analysis of Newark's modern politics since 1950, culminating with Mayor Cory Booker's rise to power and prominence both in the city and in American political consciousness. Newark's recent political history offers an interesting case study in mayoral elections, community development, and coalition building politics. While Newark is the quintessential post-industrial city, Booker has received critical attention for his post-racial politics since he frequently bypasses racial and traditional urban politics. At the same time, relations between the mayor, the municipal council, and Newark's diverse communities were often so fractious that sustainable coalition building proved to be an elusive goal to resolve longstanding crime, education, and other social problems. Based on original interviews with Cory Booker, city council members, and other prominent Newark politicians, A Post Racial Change is Gonna Come is a powerful history of how Newark became the focal point for transformative politics in urban America.
Google-Books-ID: ZRZEAgAAQBAJ
Keywords: Political Science / General; Political Science / History & Theory; Political Science / Political Economy; Political Science / Public Affairs & Administration; Political Science / Public Policy / City Planning & Urban Development; Political Science / Public Policy / General; Political Science / World / European; Science / Earth Sciences / Geography; Social Science / Ethnic Studies / General; dept.psc

The Pitch for Baseball: Washington's Plans for Nationals' Stadium - Wharton, Jonathan L. (Washington, DC's Challenges, 2005)
This is the fourth in a series of books dealing with Washington, DC. Like the first three, this also is the outgrowth of special seminars conducted in the Department of Political Science at Howard University. We examine Washington, DC's challenges, because it is vital to know the conditions under which the residents of the most powerful city in the world continue to live, based on sound empirical evidence.
Google-Books-ID: 9pVLAAAAYAAJ
Keywords: dept.psc

Unique Policymaking in Action: The District Council and the Legislative Process - Wharton, Jonathan L. (Law, Politics, and African Americans in Washington, DC, 2010)
Law, Politics, and African Americans in Washington, DC explores the legal challenges and triumphs of African Americans and law and politics in Washington, DC, a city whose majority population comprises African Americans. It examines the interconnection between law and politics in Washington, DC, because it is vital to know the legal conditions under which the African American residents of the most powerful city in the world live, based on sound empirical evidence. Law, Politics, and African Americans in Washington, DC addresses two major questions: - Why study African Americans in terms of law and politics? - Why examine law and politics at the local level, in this case Washington, DC?
Keywords: dept.pch

The WTO primer tracing trade’s visible hand through case studies - Buterbaugh, K.; Fulton, R. (Palgrave Macmillan, 2007)
This book describes the WTO from its post-WWII beginnings in the General Agreement on Tariffs and Trade through a series of negotiated enhancements of these agreements. It describes the WTO's origins, structure, and growing pains as it has had to face challenges from within and without. © Kevin Buterbaugh, 2007. All rights reserved.
Journal Abbreviation: The WTO Primer: Tracing Trade's Visible Hand Through Case Stud. Pages: 230 Publication Title: The WTO Primer: Tracing Trade's Visible Hand Through Case Stud.
Keywords: dept.psc

The Colonels' coup and the American embassy: A Diplomat's view of the breakdown of democracy in cold war Greece - Keeley, R.V.; Iatrides, J.O. (Penn State University Press, 2010)
The so-called Colonels' coup of April 21, 1967, was a major event in the history of the Cold War, ushering in a seven-year period of military rule in Greece. In the wake of the coup, some eight thousand people affiliated with the Communist Party were rounded up, and Greece became yet another country where the fear of Communism led the United States into alliance with a repressive right-wing authoritarian regime. In military coups in some other countries, it is known that the CIA and other agencies of the U.S. government played an active role in encouraging and facilitating the takeover. The Colonels' coup, however, came as a surprise to the United States (which was expecting a Generals' coup instead). Yet the U.S. government accepted it after the fact, despite internal disputes within policymaking circles about the wisdom of accommodating the upstart Papadopoulos regime. Among the dissenters was Robert Keeley, then serving in the U.S. Embassy in Greece. This is his insider's account of how U.S. policy was formulated, debated, and implemented during the critical years 1966 to 1969 in Greek-U.S. relations. © 2010 Robert V. Keeley All rights reserved.
Journal Abbreviation: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece Pages: 274 Publication Title: The Colonels' Coup and the Amer. Embassy: A Diplomat's View of the Breakdown of Democr. in Cold War Greece
Keywords: dept.psc

Disaster Response: EMDR and Family Systems Therapy under Communitywide Stress - Gelbach, R.A.; Davis, K.E.B. (Handbook of EMDR and Family Therapy Processes, 2012)
Journal Abbreviation: Handb. of EMDR and Fam. Ther. Proces.
Keywords: Communitywide stress; Disasters; Family systems therapy; Hyperarousal; Posttraumatic stress disorder; dept.psc

The United States and Greece in the twentieth century - Iatrides, J.O. (Greece in the Twentieth Century, 2013)
Journal Abbreviation: Greece in the Twentieth Century
Keywords: dept.psc

Presidential nominations in a Polarized Party System: The Republican primaries of 2012 - Paulson, A.C. (Winning the Presidency 2012, 2015)
Journal Abbreviation: Win. the Pres. 2012
Keywords: dept.psc

Occupational segregation on the playing field: The case of major league baseball - Sack, AL; Singh, P; Thiel, R (Journal of Sport Management, 2005)
Occupational segregation by race and gender, though less common now than in the past, continues to be the norm rather than the exception in the sport industry. The purpose of this study was twofold. First, occupational segregation on the baseball playing field, often referred to as stacking, was discussed in light of human capital and social closure theories. Second, an attempt was made to replicate and extend a multivariate analysis of stacking by Margolis and Piliavin (1999) that challenges the dominant social science paradigm for explaining stacking. The present study uses more recent data than the Margolis and Piliavin study, as well as multinomial logistic regression analysis. The results reveal that stacking persists in Major League Baseball. They also reveal that the effect of race/ethnicity on assignments to playing positions is reduced when one controls for skills and physical characteristics such as speed and power hitting. The implications of this finding for sport management are examined.
19 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000230501000004
Keywords: dept.psc

George F. Kennan and the birth of containment - The Greek test case - Iatrides, JO (World Policy Journal, 2005)
5 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000233048100011
Keywords: dept.psc

Conclusion: The Aegean — Life-line and Battle-line - Chircop, Aldo; Gerolymatos, André; Iatrides, John O. (The Aegean Sea after the Cold War: Security and Law of the Sea Issues, 2000)
From the dawn of the Bronze Age and Homer’s immortal epics to the latest confrontation in the Middle East and the Persian Gulf, the Aegean Sea has been critically important to countless armies of merchants, warriors, and crusaders. As a geographic entity, it is a narrow body of water dotted with islands, islets, and rocks. However, the Aegean is both a link and barrier between the Mediterranean and Black Seas, and the maritime causeway between the land masses of Europe, Asia, the Near East, and Africa. In effect, this maritime highway has been one of history’s more productive crucibles for human accomplishment, as well as an arena of conflict and destruction.
Citation Key Alias: lens.org/123-235-270-276-653, pop00241
Keywords: Geographic Entity; Greek Settlement; Narrow Body; Productive Crucible; Turkish Strait; dept.psc

Party change and the shifting dynamics in presidential nominations: the lessons of 2008 - Paulson, Arthur (Polity, 2009)
Presidential nominations in recent years have been settled with increasing speed, most of the time in the early stages of the primaries and caucuses, and certainly before the national convention, which has become more of a rally. Even when the battle for the Democratic Presidential nomination continued to the end of the primary season in 2008, it was settled before the convention. Analysts have emphasized the importance of the “invisible primary” and the front-loaded delegate selection schedule in explaining the early resolution of Presidential nomination contests. However, not enough attention has been paid to a much more fundamental change in our political parties and party system: The old umbrella parties have been replaced by ideological polarization between the parties and ideological homogenization within the parties. Our new party system dates back about forty years, and features increased ideological unity and decreased factionalism, making it easier to settle nominations. Even today's front-loaded nominating calendar would not have prevented some of the hotly contested conventions of the old umbrella parties. Polity (2009) 41, 312-330. doi:10.1057/pol.2009.4; published online 11 May 2009
5 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/170-116-037-839-141 tex.unique-id: [object Object]
Keywords: Elections; Nominations; Parties; Primaries; dept.psc

Late 19th century administrative reform in America: re-articulating Hamiltonian thought - O'Hara, Jonathan (International Review of Administrative Sciences, 2009)
In this article, the intellectual thought of a group of key late 19th century national administrative reformers is isolated and analyzed. These reformers were interested in reforming the civil, military and business administrative functions of the executive branch to provide for greater elite administrative supervision over and intervention in the national society and economy. The reformers often articulated their reform purposes, motives and goals in the Hamiltonian language of administrative authority and popular deference to executive administrative counsels. An important key to understanding this article is recognizing that while environmental social and economic conditions had changed significantly for the Gilded Age reformers since the American constitutional founding, many elements of the Hamiltonian tradition still resonated with the reformers a full century later. In this way, the historically transmitted ideology and rhetoric of Hamiltonian thought can be seen as having an independent, causative impact on the administrative reformers' purposes, motives and goals related to executive administrative reform.
0 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000263986900010
Keywords: American founding; American progressivism; Developmental democracy; Gilded Age; Mugwumps; North America; United States; administrative reform; administrative system; bureaucracy; democracy; dept.psc; legal system; nineteenth century; planning process; political ideology

The post Cold war reestablishment of effective state authority in Latin America: can 'colombianization' tame Mexico's security crisis? - Olney, Patricia (Social Science Research Network, 2009)
This paper explores the Post Cold War origins of the organized criminal violence that once gripped Colombia and now grips Mexico and particularly the highly controversial counterinsurgency strategy used in Colombia that forms the basis for the current strategy in Mexico. It argues that ideology is a reason why the military aspect of these problems was neglected for so long and the reason its detractors see it as a strategy that reduces national sovereignty and endangers democracy when statistics on control of territory, reduction of violence and democratic progress demonstrate the opposite to be true. The paper uses the term “colombianization” to emphasize Colombia’s dramatic shift from almost ungovernable to one of the most stable countries in the region. Colombianization is defined not as a counterdrug strategy as are both the Colombian and Mexican U.S. assistance strategies but as an integrated, law-based, counterinsurgency strategy implemented from the bottom up that facilitates the establishment of elite consensus and puts the country on a path toward rule of law. Ironically, it was democratic and free market reforms that strengthened the forces of instability in both Colombia and Mexico and the militarization of security that appears to facilitate democratic stability. This study uses local level assessments of Plan Colombia and local interviews conducted in Chihuahua and Michoacán to evaluate the prospects of colombianization in urban and rural Mexico. Colombia's experience suggests that colombianization can stabilize the country and help reactivate the economy but democratic progress is painfully slow and the strategy has little impact on the drug industry and the corruption associated with it.
Citation Key Alias: lens.org/096-232-138-692-720
Keywords: Patricia Olney; SSRN; The Post Cold War Reestablishment of Effective State Authority in Latin America: Can 'Colombianization' Tame Mexico's Security Crisis?; dept.psc; ⛔ No DOI found

Trade and the Environment - Buterbaugh, Kevin (Encyclopedia of Violence, Peace, & Conflict (Second Edition), 2008)
This article examines the debate over the compatibility of trade and the environment. First, it discusses the range of arguments in the debate from trade being inherently beneficial to inherently harmful to the environment. Second, the entry examines the place of the environment within the GATT/WTO and various controversies surrounding the GATT/WTO and environmental protection. Finally, the article examines the role of multilateral environmental agreements in protecting the environment and their possible consequences for the international trading system.
Citation Key Alias: lens.org/130-327-481-444-778, pop00360
Keywords: Eco-labeling; Environmental Kuznets curve; Environmental dumping; Environmental externality; Free-rider problem; GATT/WTO; Harmonization of standards; Multilateral environmental agreements; Precautionary principle; Race to the bottom; Sanitary and phytosanitary agreement; Technical barriers to trade agreement; Trade-environment debate; Trade–environment debate; dept.psc

Aristocratic and confederate republicanism in Hamiltonian thought and practice - O'Hara, Jonathan (Publius-the Journal of Federalism, 2008)
This article identifies and explores the presence of republican thought in the intellectual and policy writings of Alexander Hamilton, particularly as it applied to his theoretical understanding of the American executive branch. The article moves chronothematically, highlighting, through the Revolutionary, Constitutional, and Governmental periods of American political development, Hamilton's unique sense of republicanism with respect to international and domestic politics, as well as American political economy. The article not only attempts to demonstrate Hamilton's intellectual adherence to the republican tradition, but also his commitment to rhetorically applying the ideology to the realization of practical executive policy goals.
2 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/044-320-739-609-658 tex.unique-id: [object Object]
Keywords: dept.psc

American Republicanism and the fin-de-siècle imperialism debate - O’Hara, Jonathan (Journal of Political Ideologies, 2014)
Aristotelian republicanism rests on an important premise, that persuasion is more virtuous than coercion. Nonetheless, there is an uneasy tension between the two approaches to rule in the republican tradition. This is particularly true with respect to Aristotle’s views on foreign policy, wherein coercive means of bringing about justice among nations may be viewed as much an offspring of republican thought as the exercise of moral suasion to the same end. This article takes this interesting tension in Aristotelian republican thought and attempts to apply it as an exegetical lens for looking into the republican ideological contours of the fin-de-siècle American imperialism debate. Particular attention is paid to how the tension in republican approaches to rule informed and helped give shape to the debate. Analysed through this lens is the rhetoric of two of the debate’s most important exponents, Theodore Roosevelt, advocating greater coercive means, and Carl Schurz, an advocate of moral suasion. © 2014 Taylor & Francis.
0 citations (Crossref) [2023-10-31] Citation Key Alias: pop00444 tex.type: [object Object]
Keywords: dept.psc; foreign policy; imperialism; morality; political ideology; social justice

Male versus female career ambassadors: is the US Foreign Service still biased? - Calin, Costel; Buterbaugh, Kevin (Foreign Policy Analysis, 2019)
This paper examines the appointment of male versus female career diplomats to ambassadorial posts. We assess the role played by ambassadors' individual characteristics, including education, marital status, and number of children, and host countries' characteristics, such as quality of life and regime type, in determining if a male or female is appointed to ambassadorial positions to represent the United States in foreign countries. The time frame of this study is the entire presidencies of Bill Clinton and George W. Bush (1993-2008), during which 603 career diplomats were appointed as ambassadors. The study provides empirical evidence that there remain significant differences between women and men serving as ambassadors. Female ambassadors are more likely to be single and have no children and are less likely to be Ivy League graduates than male ambassadors. Furthermore, they are more likely to be appointed to countries with lower quality of life and better human rights records. Finally, time plays a role in the likelihood of a woman being appointed as ambassador.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000481423500004, lens.org/085-024-674-912-250 tex.address: [object Object] tex.affiliation: [object Object] tex.da: [object Object] tex.doc-delivery-number: [object Object] tex.eissn: [object Object] tex.journal-iso: [object Object] tex.keywords-plus: [object Object] tex.number-of-cited-references: [object Object] tex.publisher: [object Object] tex.research-areas: [object Object] tex.times-cited: [object Object] tex.type: [object Object] tex.unique-id: [object Object] tex.usage-count-last-180-days: [object Object] tex.usage-count-since-2013: [object Object] tex.web-of-science-categories: [object Object]
Keywords: dept.psc; peer-reviewed

Andrew Jackson - Marchant-Shapiro, Theresa (Hatred of America's Presidents: Personal Attacks on the White House from Washington to Trump, 2018)
This work examines expressions of personal hostility and animosity toward presidents―even beloved ones―throughout American history and their impact on policymaking, politics, and culture.• Investigates a unique form of expressions of hatred toward American presidents, focusing on the personal rather than the political• Covers every president from Washington to Trump• Includes coverage of personal attacks on First Families• Details how presidents and allies responded to these attacks
Keywords: dept.psc

Reexamining the Nineteenth-Century presidency and partisan press: The Case of President Grant and the Whiskey Ring Scandal - Hopper, Jennifer Rose (Social Science History, 2018)
Studies of the institutional development of the presidency and popular leadership by presidents over time lead us to contrary expectations as to how a nineteenth-century president would react to a major political scandal. Scholarship on newspapers of the late 1800s is also unclear on how a quasipartisan media, with some outlets moving toward independence, would cover a White House scandal. I find that a close analysis of the case of President Ulysses S. Grant and the Whiskey Ring scandal forces us to reconsider what we assume to be firmly modern developments in both presidential studies and media history. Though a supposedly “premodern” president, Grant still mounted a concerted effort to mitigate the damage of the scandal. Further, although the president could get his version of events across in prominent newspapers, Republican newspaper coverage was hardly reliable. Newspapers also connected politicians’ character and psychology to mistakes made in office and made presidential strategies to shape public perception clear to their audiences—emphases on political gamesmanship considered hallmarks of the modern media environment.
1 citations (Crossref) [2023-10-31]
Keywords: dept.psc; peer-reviewed

Local Mexico: Democratic Transitions in an Authoritarian Context - Olney, Patricia (FirstForumPress, a division of Lynne Rienner Publishers, Inc., 2018)
Keywords: Local government; Mexico; dept.psc; faculty_collection

Democracy in New England: a community politics reader - Wharton, Jonathan L. (Cognella Academic Publishing, 2018)
Keywords: New England; Politics and government; dept.psc; faculty_collection

Predicting revolt: Fragility indexes and the level of violence and instability in the Arab Spring - Buterbaugh, Kevin Neil; Calin, Costel; Marchant-Shapiro, Theresa (Terrorism and Political Violence, 2017)
This article is one of the first to systematically assess the ability of state fragility measures to predict violent protests and adverse regime changes in countries. We focus on the Arab Spring as an example of a situation that such measures ought to predict. Through a variety of analyses, we find that none of the measures are predictive. We then create a simple model using the literature of protest and revolts to predict both the level of violence and the extent of regime change in the Arab Spring countries. This simpler model does a better job of predicting the level of involvement in the Arab Spring than any of the complex State Fragility Indexes. Thus, the goal of this article is not to explain the causes of the Arab Spring, but to add to the discussion of the predictive value of measures of instability.
7 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000400285900008, lens.org/012-623-182-027-278 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: Arab Awakening; Arab Spring; Arab awakening; Arab spring; Political violence; Protest; State Fragility Indexes; State fragility; State fragility indexes; dept.psc; political violence; protest; state fragility

Presidential Framing in the 21st Century News Media: The Politics of the Affordable Care Act - Hopper, Jennifer Rose (Routledge, 2017)
The Patient Protection and Affordable Care Act came into existence at a time when the president’s ability to lead the public was in question, political polarization had intensified, and the media environment appeared ever more fragmented, fast-moving, and resistant to control. Under such circumstances, how can contemporary American presidents such as Barack Obama build and maintain support for themselves and their policies, particularly as controversies arise? Using case studies of major contests over how key elements of the Affordable Care Act would be framed, and analysis of how those frames fared in influential and popular U.S. news sources, Hopper examines the conditions under which the president can effectively shape public debates today. She argues that despite the difficult political and communications context, the president retains substantial advantages in framing major controversial issues for the media and the public. These presidential framing advantages are conditional, however, and Hopper explores the factors that help make presidential frames more or less likely to gain hold in the news today. More so than in the past, an element of unpredictability in this news environment means that in pursuing favorable messaging, the president and his surrogates may also generate some unintentional consequences in how issues are portrayed to the public. Presidential frames can evolve with unfolding events to take on new meanings and applications, a process facilitated alternately by supporters, opponents, and media actors. Still, media figures and political opponents remain largely reactive to presidential communications, even as some seek to publicize and exploit weaknesses in the administration’s narratives. A close look at these recent cases casts new light on the scholarly debate surrounding the president’s ability to persuasively communicate and challenges conventional wisdom that the 21st century media largely present an unmanageable news environment for the White House. Presidential Framing in the 21st Century News Media engages with current events in American politics, focusing on the Obama Administration and the Affordable Care Act, while also reflecting upon the state of the American presidency, the news media, and the public in ways that have substantial implications for all of these actors, not merely in the present, but into the future, making it a compelling read for scholars of Political Science, Media Studies, Communication Studies, and Public Policy. © 2017 Taylor & Francis.
Keywords: Public opinion; United States. Patient Protection and Affordable Care Act; Health care reform; United States; Medical policy; United States; Medicare; dept.psc; faculty_collection

Greece and the birth of containment: An American perspective - Iatrides, John O. (The Balkans in the Cold War, 2017)
America’s strategy of containment, designed to confront postwar Soviet aggression, real and perceived, grew out of a series of disparate and seemingly unrelated conflicts. Thus the clash over the future of defeated Germany was direct, immediate and of obvious importance for vital United States interests in Europe and the world. By contrast, the communist insurgency in Greece was originally perceived as a basically domestic affair of a small country in a remote region of little strategic value. Yet the Truman Doctrine, which paved the way for containment’s gradual global implementation—Marshall Plan, Berlin airlift, NATO, wars in Korea and Indochina—was ostensibly focused primarily on Greece. After remaining a benevolent but deliberately passive observer of turmoil and violence in Greece, Washington boldly replaced Britain as the foreign patron of that small and troubled Balkan state. This study documents the transformation of United States policy toward Greece, and the birth of containment. It argues that the change was fundamentally one of perceptions of the nature of Soviet policy itself within the Truman administration, rather than of realities in Greece. In retrospect, Greece was an unlikely springboard for launching the strategy of containing Moscow’s ideology and power. The significance of the communist threat in Greece was more a matter of alarmist assumptions, loose perceptions and questionable symbolism than of hard facts and geostrategic realities. But in human affairs perceptions and symbolism are important, especially if clothed in an aura of success, as was the application of containment in Greece.
Citation Key Alias: lens.org/005-990-706-119-140
Keywords: American Official; Greek Government; Military Assistance; North Atlantic Treaty Organization; Security Interest; dept.psc